Step function - a measure for frontal crash pulse and its applications. (29th October 2004) - Wu, Shen R.; Zhang, Xiangtong; Lenk, Peter
Vehicle crash is a highly nonlinear transient dynamics event. The crash pulse is among the most important quantities to describe crash behaviour. To meet the need of an analytical tool for quantifying the crash pulse, a 2-step function representation is developed based on crash test data. The essence of this method is the equivalence of occupant responses generated by the full crash pulse curve and by the simple 2-step function. The crash pulse, considered as a key for crash analysis is thus parameterised. This metric can be used to characterize the difference between 2 sets of data, from tests or CAE, the variation of test data, as well as the difference in different vehicles. A regression formula from a DOE simulation is derived and verified. The 2-step function can be used as a design tool for a quick estimate of crash test dummy responses. The parameterized regression formula has also well fitted the needs of the safety optimisation process and statistics study where the crash pulse curve plays an important role but is otherwise hard to process automatically.